2011
DOI: 10.1002/sim.4220
|View full text |Cite
|
Sign up to set email alerts
|

Assessing neural activity related to decision‐making through flexible odds ratio curves and their derivatives

Abstract: It is well established that neural activity is stochastically modulated over time. Therefore, direct comparisons across experimental conditions and determination of change points or maximum firing rates are not straightforward. This study sought to compare temporal firing probability curves that may vary across groups defined by different experimental conditions. Odds-ratio (OR) curves were used as a measure of comparison, and the main goal was to provide a global test to detect significant differences of such… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
4
0

Year Published

2011
2011
2016
2016

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(4 citation statements)
references
References 34 publications
0
4
0
Order By: Relevance
“…More conclusive evidence came with the introduction of methodological and technical approaches combining operant conditioning with electrophysiological recordings in monkeys. These studies suggested the involvement of PM in planning and execution of complex movements, motor set, preparation for and sensory guidance of movements, reorganization of movements, and learning (Roland et al, 1980; Halsband and Passingham, 1982; Weinrich et al, 1984; Halsband and Freund, 1990; Mitz et al, 1991; Passingham, 1993; Kurata and Hoffman, 1994; Wise et al, 1997) as well as in complex relations with the immediate extrapersonal space (revised in Rizzolatti and Luppino, 2001) and perceptual decision-making (Romo et al, 2004; Pardo-Vazquez et al, 2008, 2009; Lemus et al, 2009). Additionally, conjunction analysis of fMRi data has suggested the involvement of the PM cortices in processing trigeminal information (Iannilli et al, 2007).…”
Section: Generalmentioning
confidence: 99%
See 2 more Smart Citations
“…More conclusive evidence came with the introduction of methodological and technical approaches combining operant conditioning with electrophysiological recordings in monkeys. These studies suggested the involvement of PM in planning and execution of complex movements, motor set, preparation for and sensory guidance of movements, reorganization of movements, and learning (Roland et al, 1980; Halsband and Passingham, 1982; Weinrich et al, 1984; Halsband and Freund, 1990; Mitz et al, 1991; Passingham, 1993; Kurata and Hoffman, 1994; Wise et al, 1997) as well as in complex relations with the immediate extrapersonal space (revised in Rizzolatti and Luppino, 2001) and perceptual decision-making (Romo et al, 2004; Pardo-Vazquez et al, 2008, 2009; Lemus et al, 2009). Additionally, conjunction analysis of fMRi data has suggested the involvement of the PM cortices in processing trigeminal information (Iannilli et al, 2007).…”
Section: Generalmentioning
confidence: 99%
“…Although all these findings obtained with the these tasks suggested a role for the PMv in cognitive processes that can range from perception to action the first experimental evidence came from the work of Romo et al in the PMv and PMm cortices (Hernandez et al, 2002; Romo et al, 2004). They used an experimental approach that has proved very fruitful in studying the function of the posterior parietal and frontal cortices (Evarts, 1966; Fuster and Alexander, 1971; Mountcastle et al, 1975) and has allowed an identification of neurons in the PMv cortex that supports both perceptual decisions (Romo et al, 2004; Pardo-Vazquez et al, 2008, 2009; Lemus et al, 2009; Roca-Pardiñas et al, 2011) and correct and error monitoring (Pardo-Vazquez et al, 2008, 2009; Acuña et al, 2010). …”
Section: Complex Sensory–motor Interactionsmentioning
confidence: 99%
See 1 more Smart Citation
“…), electrophysiology (Roca‐Pardiñas et al. ), experimental psychology (Becker and Elliott, ) and economics (Pittau and Zelli, ; Marron and de Uña‐Álvarez, ). Ganguli and Wand () analyzed fishery data using S 3 for geostatistical data and Godtliebsen and Øigård () used Posterior Smoothing in a pattern recognition application to detect bones in fish fillets.…”
Section: Applicationsmentioning
confidence: 99%